Character Building in Supporting Teachers' Efforts to Improve Discipline in Grade 4 Students at Primary School 2 Tanjung North Lombok Regency - Made Dwipa, Lalu Belik; Mardianti, Nunung (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to analyze the role of teachers in improving the discipline of class VI students through character development at SD Negeri 2 Tanjung, North Lombok Regency. The research method used was qualitative research using observation and documentation techniques involving teachers and class VI students over several cycles. The instruments used to collect data involve observation, interviews, and document analysis. The results obtained in this research are that character development in an effort to improve discipline in grade 4 students at SD Negeri 2 Tanjung, North Lombok Regency can be implemented through several ways and methods, namely: skills development, competency-based learning, competency-based assessment, and career programs. Carried out in an integrated manner with practice in daily life (such as a remedial program), (such as a struggle program), and (such as a reflection program).